The inclusive classroom : educating exceptional children - Andrews, Jac.; Lupart, Judy. (Scarborough, OT : Nelson Thomson Learning, 2000)
Transitions in education. Students with special needs. The school-home-community partnership. Preparation for teaching and learning. Critical instruction considerations.
Keywords: Education; Special education; Special education -- Canada